Case report: Craniofrontonasal syndrome caused by a novel variant in the EFNB1 gene in a Colombian woman - Pachajoa, Harry; Vasquez-Forero, Diana Marcela; Giraldo-Ocampo, Sebastian (Frontiers in Genetics, 2023)
Craniofrontonasal Syndrome is a very rare dominant X-linked genetic disorder characterized by symptoms such as hypertelorism, craniosynostosis, eye alterations, bifid nose tip, and longitudinal ridging and splitting of nails. Heterozygous females are usually the patients severely affected. To date, clinical or genetic data have not been published for these patients in Colombia. Here we report a female proband with coronal craniosynostosis, hypertelorism, strabismus, rotational nystagmus, high-arched palate, dental crowding, scoliosis, severe pectus excavatum, unilateral breast hypoplasia, and brachydactyly; diagnosed with Craniofrontonasal Syndrome with the novel heterozygous variant c.374A>C (p.Glu125Ala) in the EFNB1 gene. So far, she has been treated with physical therapy and surgical correction of the bifid nose and an umbilical hernia. To the best of our knowledge, this is the first report of a patient with this rare genetic disorder in Colombia, expanding its mutational spectrum and highlighting the importance of genetic evaluation of patients with craniosynostosis and facial dysmorphism.